2022
DOI: 10.21203/rs.3.rs-1718587/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of a novel fully automated and ELISA- based assays for detecting anti- SARS- CoV-2 neutralizing antibodies

Abstract: Background: Rapid and accurate measurement of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2)-specific neutralizing antibodies (nAbs) is paramount for monitoring immunity in infected and vaccinated subjects. The current gold standard relies on pseudovirus neutralization tests which require sophisticated skills and facilities. Alternatively, recent competitive immunoassays measuring anti-SARS-CoV-2 nAbs are proposed as a quick and commercially available surrogate virus neutralization test (sVNT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The WHO conversion factor for the test is 1 AU = 3.31 IU/mL, and the reference range is 10–400 AU/mL. We recently evaluated this new assay and reported that it has great specificity and sensitivity in comparison to two reference techniques [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The WHO conversion factor for the test is 1 AU = 3.31 IU/mL, and the reference range is 10–400 AU/mL. We recently evaluated this new assay and reported that it has great specificity and sensitivity in comparison to two reference techniques [ 24 ].…”
Section: Methodsmentioning
confidence: 99%